2012
DOI: 10.1016/j.jcin.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Thrombectomy Versus No Thrombectomy in Patients With ST-Segment Elevation Myocardial Infarction and Thrombus-Rich Lesions

Abstract: Thrombectomy as an adjunct to pPCI in patients with high thrombus load yielded better post-procedural STR and reduced MVO at 3 months but was not associated with a reduction in infarct size and transmurality. Thromboaspiration in Patients With High Thrombotic Burden Undergoing Primary Percutaneous (Coronary Intervention; NCT01472718).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…4,5,[12][13][14][15][26][27][28][29][30][31][32][33][34][35][36][37] The weighted mean follow-up duration was 3.7±2.7 months. Three trials reported outcomes at both 1 and 12 months.…”
Section: Included Studiesmentioning
confidence: 99%
“…12,[32][33][34]37 MACE was defined in 5 studies as death, reinfarction, or target vessel revascularization. 14,15,26,27,31 In 1 study, death, reinfarction, or stroke was used as the MACE definition, 36 whereas another study used death, reinfarction, or hospitalization for heart failure as the MACE definition. 35 Another study defined MACE as composite of death from cardiovascular causes, reinfarction, cardiogenic shock, or New York Heart Association class IV heart failure.…”
Section: Included Studiesmentioning
confidence: 99%
“…В группе с применение тромбаспирацией была достигнута более быстрая резолюция сегмента ST, а также уменьшение частоты развития дистальной эмболизации и феномена "no-reflow". [9] Применение катетера Export довольно широко изучалось в различных рандомизированных исследованиях. Так, в рандомизированном исследовании EXPIRA [10], включавшем 175 пациентов, первичными конечными точками являлись снижение сегмента ST и степени миокардиального свечения.…”
Section: актуальностьunclassified